A grounded theory of organizational structures for development and infrastructure professionals in software-producing organizations - Leite, Leonardo Alexandre Ferreira (2022)
DevOps and continuous delivery have greatly impacted the organizational structures of development and infrastructure groups in software-producing organizations. Our research aims at revealing the different options adopted by the software industry to organize such groups, understanding why different organizations adopt distinct structures, and discovering how organizations handle the drawbacks of each structure. By interviewing 68 carefully-selected, skilled IT professionals and analyzing these conversations through a Grounded Theory process, we identified conditions, causes, reasons to avoid, consequences, and contingencies related to each discovered structure (segregated departments, collaborating departments, API-mediated departments, and single department). We, then, offer a theory to explain organizational structures for development and infrastructure professionals. This theory can support practitioners and researchers in comprehending and discussing the DevOps phenomenon and its related issues; it also provides valuable input to practitioners decision-making.